Global Financial Stability Report, April 2018 : A Bumpy Road Ahead. (Global Financial Stability Report; Global Financial Stability Report ;, 2018)
The April 2018 Global Financial Stability Report (GFSR) finds that short-term risks to financial stability have increased somewhat since the previous GFSR. Medium-term risks are still elevated as financial vulnerabilities, which have built up during the years of accommodative policies, could mean a bumpy road ahead and put growth at risk. This GFSR also examines the short- and medium-term implications for downside risks to growth and financial stability of the riskiness of corporate credit allocation. It documents the cyclical nature of the riskiness of corporate credit allocation at the global and country levels and its sensitivity to financial conditions, lending standards, and policy and institutional settings. Another chapter analyzes whether and how house prices move in tandem across countries and major cities around the world-that is, global house price synchronicity.